Double concerto for violon, cello and orchestra in A minor/a-Moll : - Brahms, Johannes (Eulenburg audio+score)
The Eulenburg audio+score series contains the orchestral world´s treasures from the baroque, classical and romantic reportoire. Each of the 50 volumes consists of clearly-presented and authoritative score, an informative preface detailing the biographical and creative background, and a Naxos CD containing the work in full length.